Advancements in N-heterocyclic carbenes (NHCs) catalysis for benzoin reactions: A comprehensive review from past to present - Pakin Noppawan; Baramee Phungpis; Kanokkan Worawut (Chimica Techno Acta)
N-heterocyclic carbenes (NHCs) catalyze benzoin condensation, which is a unique carbon-carbon bond-forming reaction. It entails a coupling reaction between two aldehydes catalyzed by NHCs that produce a-hydroxycarbonyl compounds (acyloins). NHCs have emerged as a potent class of organocatalysts, catalyzing numerous benzoin and benzoin-type reactions. This review provides an overview of the historical development of NHCs and their application in benzoin reactions. Additionally, recent advancements in NHC catalysis, including the use of chiral NHCs, are discussed. This review aims to provide a comprehensive understanding of the current state of NHC catalysis for benzoin reactions and its potential for future developments in synthetic chemistry.